The fluorination of C–H bonds: developments and perspectives - Gouverneur, V; Szpera, R; Moseley, D; Smith, L; Sterling, A (Wiley, 2019)
This Review summarizes the advances in fluorination via C(sp2)–H and C(sp3)–H activation. Transition metal catalyzed approaches championed by palladium have allowed the installation of a fluorine substituent at C(sp2) and C(sp3) sites exploiting the reactivity of high oxidation transition metal fluoride complexes combined with the use of directing group (some transient) to control regio‐ and stereoselectivity. The large majority of known methods employ electrophilic fluorination reagents, but methods combining a nucleophilic fluoride source with an oxidant have appeared. A number of ligands have proven to be effective for C(sp3)–H fluorination directed by weakly coordinating auxiliaries, thereby enabling control over reactivity and selectivity. Methods relying on the formation of radical intermediates are complementary to transition metal catalyzed processes as they allow for undirected C(sp3)–H fluorination. To date, radical C–H fluorinations mainly employ electrophilic N–F fluorination reagents but a unique bio‐inspired Mn(III)‐catalyzed oxidative C–H fluorination has been developed. Overall, the field of late stage nucleophilic C–H fluorination has progressed much more slowly, a state of play explaining why C–H 18F‐fluorination is still in its infancy.